2011
DOI: 10.1093/pasj/63.3.685
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of Moreton Waves

Abstract: With the Flare-Monitoring Telescope (FMT) and Solar Magnetic Activity Research Telescope (SMART) at Hida observatory of Kyoto University, 13 events of Moreton waves were captured at H$\alpha$ center, H$\alpha$$\pm$0.5 Å, and H$\alpha$$\pm$0.8 Å wavebands since 1997. With such samples, we have studied the statistical properties of the propagation of Moreton waves. Moreton waves were all restricted in sectorial zones with a mean value of 92$^\circ$. However, their accompanying EIT waves, observed simultaneously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
22
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 56 publications
7
22
0
1
Order By: Relevance
“…Thus, the "field-line valley" to the north of AR 12017 having low Alfvén speed implies a region of high compression ratio, consequently a shock wave traveling through it can produce a strong compression over the chromosphere and eventually a Moreton signature. This is in agreement with the results found by Zhang et al (2011), who analyzed the magnetic field configuration present in 13 Moreton events and concluded that the waves mostly propagate either in regions of large-scale closed magnetic loops or along valleys delimited by two sets of separated magnetic loops. Furthermore, given that close to the solar surface we expect a lower fast magneto-acoustic speed, the wavefronts will tend to curve downward, favoring compression over the chromosphere (Zhang et al, 2011).…”
Section: About the Kinematics Of The Wave Eventsupporting
confidence: 92%
See 1 more Smart Citation
“…Thus, the "field-line valley" to the north of AR 12017 having low Alfvén speed implies a region of high compression ratio, consequently a shock wave traveling through it can produce a strong compression over the chromosphere and eventually a Moreton signature. This is in agreement with the results found by Zhang et al (2011), who analyzed the magnetic field configuration present in 13 Moreton events and concluded that the waves mostly propagate either in regions of large-scale closed magnetic loops or along valleys delimited by two sets of separated magnetic loops. Furthermore, given that close to the solar surface we expect a lower fast magneto-acoustic speed, the wavefronts will tend to curve downward, favoring compression over the chromosphere (Zhang et al, 2011).…”
Section: About the Kinematics Of The Wave Eventsupporting
confidence: 92%
“…A region of open magnetic field lines can be seen in correspondence with sectors 35 -43, which sets favorable conditions for the propagation of a coronal MHD shock able to generate Moreton disturbances (Zhang et al, 2011). Furthermore, the shock speed is fundamentally determined by the coronal magnetic field value, but the compression ratio decreases with increasing magnetic field (Krause et al, 2015).…”
Section: About the Kinematics Of The Wave Eventmentioning
confidence: 79%
“…In these cases, the associated flares tend to be strong (M and X-class), but shock events were even found for C-class flares (Warmuth, 2010;Zhang et al, 2011). These flares are comparatively impulsive.…”
Section: Solar Flaresmentioning
confidence: 98%
“…A more recent study (considering the interval from 1997 March to 2001 August) gives rates of 3 and 4 waves per year for the Kanzelhöhe and Big Bear solar observatories, respectively (Warmuth et al, 2004a). Warmuth (2010) found 27 waves from 1997 to 2006 (from several observatories), which gives a rate of 4 waves per year, while Zhang et al (2011) reported 13 Moreton waves from Hida Observatory in the same time range, yielding a yearly rate of 7 waves. This means that Moreton waves occur at a rate of only ≈5% the rate of than coronal EUV waves, which implies that for the formation of a Moreton wave, more stringent conditions have to be met as compared to coronal EUV waves.…”
Section: Frequency Of Occurrencementioning
confidence: 99%
See 1 more Smart Citation